A novel star-shaped triazine-triphenylamine–based fluorescent chemosensor for the selective detection of picric acid. (June 2019) - Sathiyan, G.; Balasubramaniam, B.; Ranjan, S.; Chatterjee, S.; Sen, P.; Garg, A.; Gupta, R.K.; Singh, A.
Abstract: This work reports development of a new donor-acceptor–type star-shaped 4, 4′, 4″-(1, 3, 5-triazine-2, 4, 6-triyl)tris( N, N -diphenylaniline) (TRZDPA) molecule towards detection of an ultratrace amount of picric acid (PA). TRZDPA showed solvent-dependent fluorescence spectra in an excited state owing to its strong intramolecular charge-transfer properties. As a fluorescent probe, TRZDPA shows remarkable sensitivity towards the PA in a highly selective manner compared with other nitroaromatic compounds. Furthermore, efficiency of the quenching process was evaluated by the Stern–Volmer equation. The fluorescence quenching mechanism of the probe during PA detection was evaluated from the photophysical and other spectral characterizations. The detection limit of PA was 0.37 nM, confirming the detection of PA in aqueous media at a trace level. To facilitate easy detection of PA, TRZDPA-modified ﬂuorescent thin-layer chromatography (TLC) strips were developed as 'turn-off' sensors which can be visualized by the naked eye. Graphical abstract: Image 1 Highlights: Synthesis of a novel triazine-triphenylamine–based donor-acceptor–type star-shaped fluorescent chemosensor 4, 4′, 4″-(1, 3, 5-triazine-2, 4, 6-triyl)tris(N, N-diphenylaniline (TRZDPA). TRZDPA exhibited good fluorescence properties with long lifetime. TRZDPA showed high sensitivity and selectivity for sensing of picric acid. A colorimetric sensor which can be visualized by the naked eye.